Study onthe Effectiveness of Banana Peel and Moringa Oleifera Seed as Natural Coagulant for the Treatment of Synthetic Turbid Water - MOHD KHAIRI, NURAIN; ABDUL HAMID, NOR HAZREN (Progress in Engineering Application and Technology, 2026)
The extensive use of chemical coagulants in conventional water treatment has raised concerns related to environmental sustainability, sludge generation, and residual chemical content. This study evaluated and compared the performance of banana peel powder and Moringa oleifera seed powder as natural coagulants for turbidity removal in synthetic turbid water and real river water. Fourier Transform Infrared Spectroscopy (FTIR) analysis identified functional groups responsible for charge neutralization and adsorption, while Field Emission Scanning Electron Microscopy (FESEM) revealed distinct surface morphologies of both coagulants. Synthetic water with an initial turbidity of approximately 85 NTU, representing Class III river water under the National Water Quality Standards (NWQS), was treated using standard jar test procedures. The effects of coagulant dosage, slow mixing speed, and settling time were systematically investigated to determine optimum operating conditions. These optimum conditions were subsequently applied to Panchor River water to assess practical applicability, resulting in a significant reduction in turbidity and demonstrating the feasibility of translating laboratory-scale findings to real water treatment. The optimum dosage for Moringa oleifera seed powder was 2.0 g/L, achieving a maximum turbidity removal efficiency of approximately 96.45% at a slow mixing speed of 20 rpm and a settling time of 150 minutes. In contrast, banana peel powder achieved an optimum turbidity removal efficiency of approximately 63.69% at the same dosage of 2.0 g/L, with a slow mixing speed of 60 rpm and a settling time of 150 minutes. Overall, Moringa oleifera seed powder exhibited significantly higher turbidity removal efficiency, while both materials demonstrate potential as sustainable and environmentally friendly alternatives to chemical coagulants.